Procedures to Develop a Computerized Adaptive Testing to Advance the Measurement of Narcissistic Personality - Luo, Hao; Cai, Yan; Tu, Dongbo (Frontiers in Psychology, 2020)
As of recent, Narcissistic Personality (NP) has attracted a lot of attention. In this study, we mainly investigated the feasibility and effectiveness of using computerized adaptive testing (CAT) to measure NP (CAT-NP). The CAT in this study was simulated by the responses of several NP questionnaires of 1,013 university students as if their responses were collected adaptively. The item bank (85 items) which met the requirements of the psychometric properties of Item Response Theory (IRT) was first established, and then the CAT dynamically selects items according to the estimates of current trait level until the pre-specified measurement precision is achieved. Finally, the efficiency and validity of the CAT were verified. The results showed that the proposed CAT-NP had reasonable reliability, validity, predictive utility and high correlation. In addition, the CAT-NP could significantly save item usage without losing measurement accuracy, which greatly improves the test efficiency. The advantages and limitations of CAT in measuring NP and other psychological tests were discussed in the final section.